Cephenemyia stimulator and Hypoderma diana infection of roe deer in the Czech Republic over an 8-year period - Salaba, Ondrej; Vadlejch, Jaroslav; Petrtyl, Miloslav; Valek, Petr; Kudrnacova, Marie; Jankovska, Ivana; Bartak, Miroslav; Sulakova, Hana; Langrova, Iva (Parasitology research, 2013)
A survey of naso-pharyngeal and subcutaneous myiasis affecting roe deer (Capreolus capreolus) was conducted in the Czech Republic over an 8-year period (1999-2006). A total of 503 bucks and 264 does from six hunting localities were examined. The sampling area comprised predominantly agricultural lowlands and a mountain range primarily covered by forest. Since 1997, the deer have been treated each winter across the board with ivermectin (150 mg/kg, CERMIX® pulvis, Biopharm, CZ). Parasites found were the larvae of Hypoderma diana and Cephenemyia stimulator. There were no significant differences in warble fly infection among captured animals in the individual hunting localities. Overall, 146 (28.8%) of 503 animals (bucks) were infected with Cephenemyia stimulator larvae; body size of the second instar larva reached 13-18 mm. The prevalence ranged from 16.1 to 42.9% per year, and the mean intensity from 6 to 11 larvae per animal. Additionally, a total of 264 roe deer (does) were examined for H. diana larvae, and 77 (29.1%) were found to be positive; body size of the second instar larva reached 17 mm. The prevalence ranged from 18.8 to 50.0% per year, and the mean intensity from 13 to 22 larvae per animal. The results showed that the bot flies, Cephenemyia stimulator as well as H. diana, are common parasites in roe deer in the Czech Republic, and that through the help of treatment (ivermectin), it is possible to keep parasite levels low. The body weights of infected and non-infected H. diana deer did not differ significantly.
Keywords: subkutánní tkáň; nazofarynx; prevalence; Animals; Myiasis; Ivermectin; Nasopharynx; Prevalence; zvířata; Subcutaneous Tissue; vysoká zvěř; Diptera; myiáza; ivermektin; Czech Republic; Deer; Česká republika